KINERJA LAYANAN ADMINISTRASI PEMERINTAH DESA SUKA MAKMUR KECAMATAN BULANGO ULU KABUPATEN BONE BOLANGO - Muh Fachri Arsjad; Nirmala A. Sahi; Dikson Junus; Muten Nuna; Nikma Bilondatu (Mimbar Administrasi Mandiri, 2024)
This research was conducted to determine the performance of government administration in Suka Makmur Village, Bulango Ulu District. This research is qualitative research, namely a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. The results of this research indicate that the performance of government administration in Suka Makmur Village, Bulango Ulu District is quite good, which can be seen from several administrative service performance indicators used, namely: 1) Tangibles, where in principle the government administration service facilities in Suka Makmur Village are sufficient adequate; 2) Reliability, where Suka Makmur Village government officials have quite good administrative service work capabilities; 3) Responsiveness, Suka Makmur Village government officials are always responsive in carrying out administrative service tasks in the village; 4) Assurance, Suka Makmur Village government officials always provide certainty and clarity regarding administrative service times in the village and 5) Empathy, Suka Makmur Village government officials always treat the community well, politely and courteously. The recommendation of this research is that the Suka Makmur Village Government, Bulango Ulu District, continues to pay attention to and improves the quality and capabilities of village government officials, by continuing to involve officials in various training activities, in order to increase the insight and work experience of the village government officials themselves, then continue to maintain work enthusiasm, by continuing to provide professional administrative services and continuing to pay attention to and maintain a good work ethic, as well as a strong attitude and mentality in serving the community.